Social impact assessment of biofuel production for maritime and aviation sectors: a case study of a pilot biorefinery project - Kostidi, Evanthia; Lyridis, Dimitrios (Frontiers in Energy Research, 2024)
This work presents a comprehensive Social Life Cycle Assessment (S-LCA) and Social Cost-Benefit Analysis (S-CBA) conducted as part of a research project, studying biofuel production for the maritime and aviation sectors, from various types of non-food waste biomasses. The inclusion of social considerations complements and expands on the environmental and economic ones. The importance of social group criteria was determined through expert questionnaires, leading to the identification of social impacts groups and social criteria from stakeholders across participating countries. The results successfully identified and quantified social impacts, and align with those reported in similar cases in relevant literature. Social Cost-Benefits, monetarizing social factors, demonstrated several social benefits, including reduction in Greenhouse Gas Emissions. However, it also highlighted social costs, such as Economic Costs associated with the initial investment. The study revealed critical social hotspots within the impact categories, making significant strides in understanding the social impacts of biofuel production, providing valuable insights for decision-makers, and contributing to the broader goal of sustainable and socially responsible biofuel production.